1997
DOI: 10.1074/jbc.272.49.30889
|View full text |Cite
|
Sign up to set email alerts
|

Low Affinity Interaction of Human or Rat T Cell Adhesion Molecule CD2 with Its Ligand Aligns Adhering Membranes to Achieve High Physiological Affinity

Abstract: The mechanism by which low affinity adhesion molecules function to produce stable cell-cell adhesion is unknown. In solution, the interaction of human CD2 with its ligand CD58 is of low affinity (500 mM ؊1 ) and the interaction of rat CD2 with its ligand CD48 is of still lower affinity (40 mM ؊1 ). At the molecular level, however, the two systems are likely to be topologically identical. Fluorescently labeled glycosylphosphatidylinositol-anchored CD48 and CD58 were prepared and incorporated into supported phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
194
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(210 citation statements)
references
References 50 publications
15
194
1
Order By: Relevance
“…For murine CD2-CD48 interactions, the two-dimensional affinity barely supports the formation of molecular contacts between cells and model planar membranes when the proteins are at physiological densities (54). It therefore cannot necessarily be concluded that the extracellular domains of proteins with solution dissociation constants higher than 75 µM will spontaneously interact at physiological densities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For murine CD2-CD48 interactions, the two-dimensional affinity barely supports the formation of molecular contacts between cells and model planar membranes when the proteins are at physiological densities (54). It therefore cannot necessarily be concluded that the extracellular domains of proteins with solution dissociation constants higher than 75 µM will spontaneously interact at physiological densities.…”
Section: Discussionmentioning
confidence: 97%
“…In this complex, CD2 and CD58 each dock at structurally equivalent sites centred on the and II, respectively. The more relevant parameter, however, is the "two-dimensional" affinity which allows comparisons of interactions between proteins confined within adjacent lipid bilayers (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the seminal work of Bell (8), many authors have considered how receptor-ligand binding in the membrane environment will differ from the same interactions measured in solution (9)(10)(11)(12)(13). All of these studies consider the generic physical effects of confining receptors and ligands to two apposed cell membranes.…”
mentioning
confidence: 99%
“…Rough cells initially may form isolated point contacts that over time might be broadened and connected through active membrane processes (2). Alternatively, the cells may simply possess inherently smooth surfaces capable of broad initial contacts.…”
mentioning
confidence: 99%